1982
DOI: 10.1111/j.1365-2222.1982.tb01645.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin reactivity, basophil degranulation and IgE levels in ageing

Abstract: Skiti tests with histamine, the histamine-liberator, codeine, and various allergens as well as blood basophil degranulation by anti-IgE or anti-IgG4 and total serum IgE levels have been studied in two female populations of different ages (average 23-1 and 73-9 years). All thirty-one patients selected for this study were clinically non-allergic.We observed a trend towards reduced skin reactions to histamine and codeine in the higher age-group; on the other hand, we could not find any decrease of basophil degran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…A trend toward decreased production of superoxide anions was also observed in eosinophils from old individuals, but eosinophil adhesion, chemotaxis, and number in the sputum were unchanged. Basophil degranulation was initially reported to be impaired in an aged cohort [72], while a later study found higher reactivity from basophils from old subjects for both the maximum proportion of anti-IgE-induced histamine release as well as sensitivity to a standard concentration of anti-IgE [73]. With the recent demonstration of roles for basophils in CD4 TH2 cell differentiation [74] and in enhancing humoral immune memory responses [75], studies in aging humans are needed to examine these newly discovered functions.…”
Section: Neutrophils Eosinophils and Basophilsmentioning
confidence: 99%
“…A trend toward decreased production of superoxide anions was also observed in eosinophils from old individuals, but eosinophil adhesion, chemotaxis, and number in the sputum were unchanged. Basophil degranulation was initially reported to be impaired in an aged cohort [72], while a later study found higher reactivity from basophils from old subjects for both the maximum proportion of anti-IgE-induced histamine release as well as sensitivity to a standard concentration of anti-IgE [73]. With the recent demonstration of roles for basophils in CD4 TH2 cell differentiation [74] and in enhancing humoral immune memory responses [75], studies in aging humans are needed to examine these newly discovered functions.…”
Section: Neutrophils Eosinophils and Basophilsmentioning
confidence: 99%
“…The frequency of autoimmune diseases is augmented with age, too, accompanied by an increase in autoantibodies, which is, interestingly, not observed in centenarians [ 60 , 61 ]. On the other hand, specific IgE production decreases, reducing the risk for allergies [ 62 , 63 ].…”
Section: Reviewmentioning
confidence: 99%
“…In addition, basophils express Toll-like receptor (TLR) 2 and TLR4, and respond to microbial ligands like peptidoglycan [ 13 ] and lipopolysaccharide (LPS) [ 14 ]. Histamine release and sensitivity of basophils from elderly were reported to be increased upon anti-immunoglobulin (Ig) E stimulation [ 15 ], but in a different study, no age-related difference was found in histamine release of human blood basophils upon anti-IgE or anti-IgG4 stimulation [ 16 ]. Basophil counts were not associated with frailty or mortality in elderly women [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%